Jogos, sociabilidade e conflito no Brasil - Édison Gastaldo; Everardo Rocha; Adriana Braga (Ciências Sociais Unisinos)
Games, competitions and plays are some of the most constant phenomena of human experience. According to the classic formulation of Johan Huizinga’s Homo ludens (from 1938), culture itself would derive its fundamental features from the elementary structure of play. To him, poetry, law, war, music, religion and everything we regard as serious, sacred and respectful derive at some level from ancient sacred games, and still keep their elementary features. In social theory, the participation in games and competitions usually highlights their symbolic, ritual and communicational aspects, as well as their links to wider sociability networks. However, it should be noted that game-like situations show a great potential for the expression of social dramas, as they develop the passion they raise out of the dramatic tension of the conflicts they represent. In this paper, starting from two ethnographic experiences, we wish to explore the symbolic dimension of ordinary participation in games in Brazilian culture.